Analysis Of Consumer Repurchase Intention On Shopee E-Commerce Using The TAM Approach: Consumer Satisfaction As A Mediator - Forever, Febiwenesya; Yutika, Fitri (Jurnal Ekonomi, 2024)
During the COVID-19 pandemic, people changed their shopping patterns to meet daily needs. One of the changes is the increase in online shopping. Both society and the business world have increasingly adapted to many changes in the post-pandemic period. Various online shopping sites have emerged, including several e-commerce platforms widely used by Indonesian society. The purpose of this research is to examine the influence of perceived ease of use and perceived usefulness on repurchase intention on the e-commerce platform Shopee in Pontianak through the mediating role of customer satisfaction. This research employs a quantitative method, with data collected through online questionnaires using Google Forms. The population of this study consists of consumers who have made online purchases via the Shopee e-commerce platform. The sampling technique used is purposive sampling, and 148 respondents were obtained. Data analysis was performed using partial least squares structural equation modeling (PLS-SEM) with the tool SmartPLS 3.0. The results of this study show that there is an influence of perceived ease of use and perceived usefulness on customer satisfaction, each with values of 0.025 and 0.000, indicating significance. Additionally, there is a mediating role of customer satisfaction in the relationship between perceived usefulness and repurchase intention, with a p-value of 0.000.